Casein Kinase II Phosphorylation-induced Conformational Switch Triggers Degradation of the Papillomavirus E2 Protein - Penrose, Kerri J. (2004)
The major phosphorylation sites of the bovine papillomavirus E2 transactivator protein are two serine residues, 298 and 301, that are located in a flexible hinge region between the DNA binding and transactivation domains. Phosphorylation of serine residue 301 promotes ubiquitination and rapid degradation of the E2 protein by the proteasome pathway. To understand the mechanism through which phosphorylation regulates the intracellular levels of this unique papillomavirus regulatory protein, we have carried out an extensive mutational analysis of the region surrounding the phosphorylation sites of the E2 protein. Our results indicate that casein kinase II phosphorylates serine 301. However, phosphorylation of serine 301 is not a sufficient recognition motif for proteasomal degradation; other residues that directly surround the phosphorylation sites are crucial for E2 degradation. The phenotypes of E2 proteins mutated in this region indicate that phosphorylation of serine 301 induces a conformational change that leads to degradation of the E2 protein. In support of this model, circular dichroism studies of the conformational tendencies of peptides from this region indicate that phosphorylation at position 301 decreases the local thermodynamic stability of this region. Thus, this region appears to have evolved to display a marginal local thermodynamic stability that can be regulated by phosphorylation, leading to targeted degradation of the E2 protein.